Rationalist usage of non-steroidal anti-inflammatory drugs in osteoarthritis [Osteoartritte steroid olmayan antiinflamatuvar ilaçlarin akilci kullanimi] - (:unkn) unknown (My University, 2005)
Osteoarthritis (OA) is the most common joint disorder with a mean prevalence of 10-12% in different populations. It is also the most frequent cause of musculoskeletal disability and pain in elderly people. The treatment of OA is complex including non-pharmacological, pharmacological and intra-articular treatments. Particularly pharmacological treatment modalities should be adapted to individual response to treatment, tolerability, side effects and disease progression. While differences exist, most treatment guidelines recommend paracetamol as the initial oral drug for OA, based on its efficacy, tolerability, and cost. In patients who respond inadequately to paracetamol, supplementary or replacement with non-steroidal anti-inflammatory drugs (NSAIDs) is recommended. Since coexisting systemic diseases are common in the elderly population having symptomatic OA as well, additional introduction of NSAIDs can lead problems regarding polypharmacy. It is known that NSAIDs have also the potential for serious gastrointestinal, renal, and cardiovascular toxicities which should always be taken into consideration before their use in elderly patients, and those having risks. Therefore the lowest even nonprescription effective doses should be considered for the shortest duration. New NSAIDs, that act as specific inhibitors of the cyclo-oxygenase-2 enzyme (COX-2 inhibitors or coxibs) have shown similar efficacy to that of NSAIDs in the treatment of osteoarthritis but with gastrointestinal toxicity comparable with that of placebo. Although these novel NSAIDs were mostly recommended in old patients or those having the risk to experience side effects, recent publications demonstrated increased risk of serious cardiovascular toxity. On the light of new data expected from ongoing randomized controlled trials on the safety of both classical NSAIDs and coxibs, it seems that new advises would appear in near future in the pharmacological treatment guidelines for OA.
Keywords: Non-steroidal anti-inflammatory drugs; Osteoarthritis